Formation of crystalline multimetallic layered double hydroxide precipitates during uptake of Co, Ni, and Zn onto γ-alumina: Evidence from EXAFS, XRD, and TEM. (November 2022) - Gou, Wenxian; Mo, Xinxin; Ren, Chao; Wang, Hongtao; Li, Wei
Abstract: While the phenomenon of surface adsorption of heavy metals occurring at the mineral-water interface is well understood, the mechanisms of surface precipitation in controlling the fate of heavy metals in soils and water have not been clearly addressed. In this research, we used a combination of extended X-ray absorption fine structure (EXAFS) spectroscopy, high-resolution transmission electron microscopy (HRTEM), and X-ray diffraction (XRD) to determine the uptake mechanisms of Co, Ni, and Zn on γ-Al2 O3 at pH 7.5. EXAFS analysis revealed the formation of multimetallic layered double hydroxides (LDHs), and the Me–Me distances (Me = Co, Ni, and Zn) of the multimetallic LDH were inversely correlated with the molar ratio of the sorbed Ni and the sorbed total metals. The HRTEM analysis showed that flake or needle-like shapes of the LDH precipitate formed at the nanoscale. Additionally, XRD suggested that these multimetallic LDHs were crystalline, and the crystallinity was dependent on the heavy metal type. This provides, for the first time, experimental evidence for the formation of CoNiZn–Al LDH precipitates at mineral-water interfaces. These results have pronounced environmental implications in heavy metal remediation, reactive transport modeling, and environmental risk assessment. Graphical abstract: Synopsis: Simultaneous uptake of Co, Zn, and Ni leads to the formation of mixed-metal precipitates. Image 1 Highlights: The macroscopic sorption of Co, Ni, and Zn is neither promoted nor inhibited by each other during cosorption on γ-Al2 O3 surfaces at pH 7.5. Co, Ni, and Zn precipitate as monometallic LDHs with single element addition but as multimetallic LDHs when added simultaneously. Multimetallic LDHs differ in chemical composition and crystallinity relative to the relevant monometallic LDHs.